Global Experiences of Community Responses to COVID-19: A Systematic Literature Review - Yijin Wu; Quan Zhang; Quan Zhang; Meiyu Li; Qingduo Mao; Linzi Li (Frontiers in Public Health, 2022)
ObjectiveThis study aimed to conduct a systematic review of the global experiences of community responses to the COVID-19 epidemic.MethodFive electronic databases (PubMed, Embase, CINAHL, ScienceDirect, and Web of Science) were searched for peer-reviewed articles published in English, from inception to October 10, 2021. Two reviewers independently reviewed titles, abstracts, and full texts. A systematic review (with a scientific strategy for literature search and selection in the electronic databases applied to data collection) was used to investigate the experiences of community responses to the COVID-19 pandemic.ResultsThis review reported that community responses to COVID-19 consisted mainly of five ways. On the one hand, community-based screening and testing for Coronavirus was performed; on the other hand, the possible sources of transmission in communities were identified and cut off. In addition, communities provided medical aid for patients with mild cases of COVID-19. Moreover, social support for community residents, including material and psychosocial support, was provided to balance epidemic control and prevention and its impact on residents' lives. Last and most importantly, special care was provided to vulnerable residents during the epidemic.ConclusionThis study systematically reviewed how communities to respond to COVID-19. The findings presented some practical and useful tips for communities still overwhelmed by COVID-19 to deal with the epidemic. Also, some community-based practices reported in this review could provide valuable experiences for community responses to future epidemics.